High-temperature compressive properties and tribological behaviour of Mo2NiB2–Ni cermets. Issue 15 (15th October 2019) - Zhang, L.; Huang, Z.F.; Shen, Y.P.; Li, K.M.; Cao, Z.; Jian, Y.X.; Ren, Z.J.
Abstract: The present work investigated the high-temperature compressive strength and tribological behaviours of Mo2 NiB2 –Ni cermets from 25 to 900 °C. Mo2 NiB2 –Ni cermets with four different Ni additions were first fabricated successfully and then tested. The results show that cermets with Ni/B 1.1 have the best compressive strength of 531.8 MPa at 900 °C and superior strength retention at high temperature. With the best high-temperature compressive strength, Mo2 NiB2 –Ni cermets with Ni/B 1.1 are used as pins with Si3 N4 disks in a tribological test. The wear rate of Mo2 NiB2 –Ni cermets gradually increases as the temperature increases from 25 to 900 °C, while the friction coefficient shows the opposite trend. Within the entire testing temperature range, the friction coefficient decreases, and the minimum friction coefficient is obtained at 900 °C. The decline of the friction coefficient is attributed to the self-lubricating oxidation tribolayer covering the worn surface. Moreover, the dominant wear mechanism changes from abrasive wear to oxidation wear as the temperature exceeds 600 °C.